E-Commerce Implementation in SMIs To Support Denpasar as a Local Culture-Based Smart City In Bali Province - Ni Nyoman Yuliarmi; Ni Putu Martini Dewi; Made Ika Prastyadewi (Cita Konsultindo Research Center, 2023)
Local governments rely on small and medium industries (SMIs) as the economic foundation in generating income s to achieve equitable and sustainable economic growth. As an Indonesian competent and cultured smart city, Denpasar City is preparing itself to become a smart city to respond to current global challenges. In this respect, SMIs play a crucial role in supporting Denpasar City's efforts to become a smart city and realize its vision of a culture-based, creative, and harmonious city. They improve public welfare and create job opportunities and enhance public income. This study seeks to: 1) analyze the impact of capital on e-commerce implementation in Denpasar City's SMIs, 2) analyze the impact of production units on e-commerce implementation in Denpasar City's SMIs, 3) examine the impact of business age on e-commerce implementation in Denpasar City's SMIs, and 4) examine the impact of income on e-commerce implementation in Denpasar City's SMIs. Our population is the entire SMIs in Denpasar City (4,074 units) (Bali Province's Industry and Trade Provincial Office, 2018). Slovin's formula (margin of error of 7 percent) generates a sample of 194 SMI units. Each SMI is represented by its owner as the respondents. We use stratified random sampling based on geographical areas (subdistricts) and accidental sampling to select sample units to be interviewed. The results demonstrate that 1) capital does not positively affect e-commerce implementation in Denpasar City's SMIs, 2) production units do not significantly affect e-commerce implementation in Denpasar City's SMIs, 3) business age positively affects e-commerce implementation in Denpasar City's SMIs, and 4) income positively affects e-commerce implementation in Denpasar City's SMIs.